177k views
2 votes
Solve, using the substitution method.

m + n = 5

m – n = 3



There is no solution.




The solution is (2, –1)



The solution is (4, 1)



There are an infinite number of solutions.

User Megaroeny
by
4.7k points

2 Answers

10 votes

Explanation:

m-n = 3 becomes m=3+n

Substitute 3+n to m in m+n = 5

Therefore;

3+n+n = 5

3 + 2n = 5

2n = 2

n = 1

m - n = 3, n is 1

therefore;

m - 1 = 3

m = 4

User Muntasir
by
4.9k points
3 votes

Answer:

your answer will be (4,1)

Explanation:

i took the quiz :)

have a great rest of your day/night :)

User Mahmoud Odeh
by
4.3k points